Legal Scope of Human Cloning: Comparative Analysis Between the United Kingdom and France - Wan Nurainun Najwa Sulaiman; Muh Endriyo Susila (Yuridika, 2023)
"Reproductive" cloning and "therapeutic" or "research" cloning are both deliberate attempts to create humans that are genetically identical. Human reproductive cloning in general is prohibited by a number of international and regional agreements, including the Charter of Fukushima, the Additional Protocol of the Council of Europe to the Convention on Human Rights and Biomedicine, the World Health Organization resolutions on the implications of cloning for human health, and the Universal Declaration on the Human Genome and Human Rights. However, there are some countries that want to explore therapeutic cloning and cannot, therefore, support a general ban on cloning. This paper aims to review the legal position of human cloning in the UK and France and further compares the issue between the two countries. the legal position of human cloning in the UK and France, it is clear that both countries were initially against the idea and concept of human cloning in general. Human cloning is a much-needed technology, especially in these modern times. Every day we encounter new diseases and illnesses, so human cloning is essential to help us be better prepared for the future.